ELECTRONIC WORD OF MOUTH ANDA RELIGIOSITY ON PURCHSE INTENTION: THE MODERATING ROLE OF BRAND HATE AMONG STARBUCKS CONSUMERS IN INDONESIA - Shilmy Diyani; Putu Nina Madiawati; Nurafni Rubiyanti (PT. Jurnal Center Indonesia Publisher, 2026)
The emergence of consumer boycotts driven by socio-political issues reflects a fundamental shift in consumer behavior in the digital era. In Indonesia, a country characterized by high religiosity and extensive social media engagement, the rapid dissemination of negative information through electronic word of mouth (e-WOM) can trigger strong emotional reactions toward brands. Starbucks Indonesia represents a salient case in which the brand became associated with the Israel–Palestine conflict, generating moral debates, religious sentiments, and intense brand-related hostility in digital spaces. In this context, consumers act not merely as rational economic actors, but as moral agents whose purchasing decisions are influenced by deeply held values and beliefs. This study aims to examine the effects of e-WOM and religiosity on purchase intention, with brand hate serving as a moderating variable among Starbucks consumers in Indonesia. Specifically, the research investigates how exposure to negative online narratives and consumers’ religiosity shape emotional responses in the form of brand hate, and how these responses influence purchasing intentions within a boycott context. A quantitative research design was employed using a survey method targeting Starbucks consumers in Indonesia who were aware of the boycott related to the Israel–Palestine conflict. Data were collected through structured questionnaires and analyzed using structural equation modeling to assess both direct and indirect relationships among variables, including the moderating role of brand hate. This approach enables a comprehensive understanding of the psychological and behavioral mechanisms underlying consumer responses to value-laden and morally sensitive issues. The findings reveal that electronic word of mouth has a significant effect on purchase intention. Religiosity also influences purchase intention, both directly and indirectly through the formation of brand hate. Moreover, brand hate significantly moderates the relationship between e-WOM and purchase intention, such that higher levels of brand hate intensify the decline in consumers’ willingness to purchase. These results highlight the critical role of morally driven negative emotions in explaining reduced purchase intention during boycott movements. This study contributes theoretically by extending consumer behavior literature through the integration of digital communication, religiosity, and negative brand emotions within a single conceptual framework. Practically, the findings suggest that global brand managers should adopt culturally and religiously sensitive communication strategies and proactively manage digital narratives to mitigate the escalation of brand hate amid socio-political controversies.